Menentukan Masa Minimum Antara Peristiwa (MIT) Curahan Hujan Dengan Menggunakan Kaedah Nix - Mohd Basri, Noor Erdhiha; Nojumuddin, Nur Syereena (Research in Management of Technology and Business, 2020)
Rainfall details are essential for effective water resource management especially in operating hydraulic structures. In Malaysia, the frequency of floods, especially in urban areas, causes huge losses and damage to property and the environment. Rainfall generation models are very important as historical data sets are often inadequate. As such, this study uses the Nix method approach to achieve the objectives of the study. Therefore, 10 years of rainfall data from 2005 to 2014 in the States of Kelantan and Terengganu have been used to determine the minimum inter-event time (MIT) to isolate the rainfall events. This analysis is applied using Dev-C ++ software that has been programmed to facilitate the analysis of rainfall data. The results of the study found that the appropriate MIT values ​​for Kelantan and Terengganu are 8 hours and 9 hours, respectively.